Antecedents of Organizational Citizenship Behavior Among Educators in Language Education for Adult Immigrants in Norway. (February 2013) - Elstad, Eyvind; Christophersen, Knut-Andreas; Turmo, Are
Organizational citizenship behavior (OCB) is discretionary and is neither directly nor explicitly recognized by the formal reward system. OCB promotes the efficient and effective functioning of a school organization. The purpose of this article is to explore the antecedents of OCB among educators of adult immigrants in Norway and to examine the relative impact of these aspects on OCB. The study is rooted in theories that have their focal point in employees' perceptions of exchange. The methodology involved was a cross-sectional survey of 764 educators. The structural equation analysis indicated that factors such as relational trust between the leader and educators and perceptions of social exchange have a strong positive effect on the educators' OCB. The article concludes with a discussion of how social practice among educators and school leaders is mobilized for sustained extra-role behavior that is advantageous to the organization.